101k views
1 vote
Please help!
Simplify the expression using order of operations:25 - 5 + 36/9 - 6(7)

User Gambit
by
4.7k points

2 Answers

6 votes

Answer:

-18

Explanation:

start with the figure in brackets. 6(7)=42

then do division. 36/9=4

our expression now is 25-5+4-42

addition first 25+4=29

finish with subtraction. 29-5-42=-18

answer=-18

User Letitbe
by
4.9k points
4 votes

Answer:

-18

Explanation:

Follow these steps to get your answer!

Divide 36/9 and multiply -6(7)

25 - 5 + 4 - 42

Subtract 25-5

20 + 4 -42

Add 4 to 20.

24-42

Subtract 42 from 24.

-18

User StatusReport
by
4.7k points